ERROR ANALYSIS IN WRITING RECOUNT TEXT - Agustina, Tri (JoLLIET, 2016)
The study aims to identify the types of morphological, syntactic, discourseerror in writing recount text by the eighth grade students of SMPMuhammadiyah 4 Surakarta. In addition, it is to know the frequency of eachtype of errors, to know the dominant type of error and to know the sources ofthe errors.The type of research is qualitative research. The method ofcollecting data is elicitation method, which is divided into four steps: first steps arerequesting the learner to make recount text with the theme that has given; second step is reading the recount text made by students; third step isfinding and marking error in the recount text; and last step is dividing theerror into the types of error based on linguistic category and surface strategytaxonomy.Foranalyzing the data,the writer takes six steps, namely:identification of errors, classifying into error types, describing the frequencyof error, describing the dominant type of error, analysis of the sources oferror and describing the purposed remedial teaching. The result of researchshows that lexical errors is 22,2% including false friends, wrong spelling anduse of Indonesian word. Syntactical error is 64% which includes verb(omission of verb, misuses of verb in past tense, addition of to in verb ofpresent tense addition of verb), noun (omission of {-s} plural marker,addition of {-s}), BE (omission of be, misuses of be), phrase (misorderingnoun phrase)), article (addition of article), preposition (addition ofpreposition, omission of preposition), sentence construction(omission ofsubject, literal translation of Indonesian). Discourse error is7,7% whichinclude generic structure. The dominant type of error is wrong spelling andmisuses of verb in past tense.Key words: error analysis, linguistic category taxonomy, recount text,surface strategy